Docking Studies and Anti-inflammatory Activity of Î²-Hydroxy-Î²-arylpropanoic Acids - Ivan O. Juranic; Sote M. Vladimirov; Bojan D. Markovic; Zorica D. Juranic; Silva Lj. Dobric; Sanda P. Dilber (Molecules, 2008)
The article describes a two-step synthesis of diastereomeric 3-hydroxy-2-methyl-3-(4-biphenylyl)butanoic acids. In the first step an intermediate Î±-bromo propanoicacid 1-ethoxyethyl ester was synthesized. The second step is a new modified Reformatskyreaction in presence of Zn in tetrahydrofuran (THF) at â5 to 10 Â°C between the previouslysynthesized intermediate and 4-acetylbiphenyl. Synthesis of the other studied Î²-hydroxy-Î²-arylpropanoic acids has already been reported. These Î²-hydroxy-Î²-arylpropanoic acidsbelong to the arylpropanoic acid class of compounds, structurally similar to the NSAIDssuch as ibuprofen. The anti-inflammatory activity and gastric tolerability of thesynthesized compounds were evaluated. Molecular docking experiments were carried outto identify potential COX-2 inhibitors among the Î²-hydroxy-Î²-aryl-alkanoic acids class.The results indicate that all compounds possess significant anti-inflammatory activity afteroral administration and that the compounds 2-(9-(9-hydroxy-fluorenyl))-2-methylpropanoic acid (5) and 3-hydroxy-3,3-diphenyl-propanoic acid (3) possess thestrongest anti-inflammatory activity, comparable to that of ibuprofen, a standard NSAID,and that none of tested substances or ibuprofen produced any significant gastric lesions.